Amelioration of Citrobacter rodentium proliferation in early stage of infection in mice by pretreatment with Lactobacillus brevis KB290 and verification using in vivo bioluminescence imaging. Issue 6 (9th November 2016) - Waki, Naoko; Kuwabara, Yuki; Yoshikawa, Yuko; Suganuma, Hiroyuki; Koide, Hiroyuki; Oku, Naoto; Ohashi, Norio
Abstract: Bioluminescent imaging (BLI) has become a useful tool for monitoring bacterial infections in real time. Citrobacter rodentium and its BLI are widely used as a murine model of enteropathogenic and enterohaemorrhagic Escherichia coli infection. In this study, we evaluated the protective effects of the probiotic Lactobacillus brevis KB290 against C. rodentium infection by the BLI approach. First, we examined several solutions for making the suspension of bioluminescent C. rodentium for an oral inoculation to establish a stable intestinal infection. Three percent NaHCO3 solution was found to be the best. Subsequently, mice were orally administered KB290 once daily for 7 days before inoculation with bioluminescent C. rodentium and for 8 days after infection. The bioluminescence intensity of mice fed with KB290 was significantly lower than that of unfed mice on days 1–3 after infection. The mRNA levels of tumour necrosis factor-α and interferon-γ in the distal colon from KB290-fed mice were shown to be significantly higher than those from unfed mice on day 3 after infection. The results suggested that KB290 intake partially inhibited the proliferation of C. rodentium, especially in the early stages of infection, viathe moderate enhancement of tumour necrosis factor-α and interferon-γ production in the colon. Abstract : In vivo bioluminescence imaging revealed that probiotic Lactobacillus brevis KB290 inhibited the proliferation of Citrobacter rodentium, an enteric bacterial pathogen, especially in the early stage of murine infection.